Treatment of walking impairment in multiple sclerosis with dalfampridine - Andrew R. Blight (Therapeutic Advances in Neurological Disorders, 2011)
Potassium channel blockade has long been considered a potential therapeutic strategy for treatment of multiple sclerosis (MS) based on the pathophysiology of demyelinated axons. Dalfampridine, which is also known as fampridine or 4-aminopyridine (4-AP), is the potassium channel blocker that has been studied most extensively in MS and other demyelinating neurologic disorders. An extended-release formulation of dalfampridine was recently approved by the US Food and Drug Administration to improve walking in patients with MS. In randomized, double-blind, placebo-controlled trials, with dalfampridine extended release tablets 10 mg taken twice daily, about 12 h apart, walking speed was improved in approximately one-third of treated patients; in these patients, average walking speed on therapy was about 25% above baseline. This improvement was clinically meaningful as assessed by concurrent measurement of patient-reported severity of walking-related disability. Dalfampridine extended release tablets were generally well tolerated, with a range of adverse effects that appear to be related to increases in central nervous system excitation. There is a dose-dependent increase in the occurrence of seizures at doses higher than the recommended 10 mg twice daily.